(untitled) (Heritage, 2024)
This paper delves into the interpretation of Plato’s political philosophy as presented by Slobodan Jovanović, a prominent professor and dean of the Faculty of Law, rector of the University of Belgrade, president of the Serbian Royal Academy of Sciences, and Prime Minister of the Kingdom of Yugoslavia in exile. Jovanović’s extensive body of work includes research on 19th-century national political history, state and law theory, constitutional law, political sociology, and the history of political theories. Despite his comprehensive scholarly contributions, this aspect of Jovanović’s work has not been thoroughly explored. Alongside his studies on the political, economic, and social doctrines of figures like Niccolò Machiavelli, Edmund Burke, Karl Marx, Friedrich Engels, Benjamin Constant, Hans Kelsen, and other anti-Marxist theorists, Jovanović also dedicated significant attention to ancient political philosophy, particularly the works of Plato.